2013
DOI: 10.1111/pbi.12080
|View full text |Cite
|
Sign up to set email alerts
|

Chrysanthemum expressing a linalool synthase gene ‘smells good’, but ‘tastes bad’ to western flower thrips

Abstract: Summary Herbivore‐induced plant volatiles are often involved in direct and indirect plant defence against herbivores. Linalool is a common floral scent and found to be released from leaves by many plants after herbivore attack. In this study, a linalool/nerolidol synthase, FaNES1, was overexpressed in the plastids of chrysanthemum plants (Chrysanthemum morifolium). The volatiles of FaNES1 chrysanthemum leaves were strongly dominated by linalool, but they also emitted small amount of the C11‐homoterpene, (3E)‐4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 44 publications
3
48
0
Order By: Relevance
“…The linalool conjugates were exclusively detected as putative linalyl-hexose and linalyl-malonyl hexoses, as previously observed Yang et al, 2013). They accumulated at up to 5 times higher concentrations in the cyp76c1 lines, and their levels were significantly reduced in the complemented/35S:CYP76C1 line compared with the wild type ( Figure 6; Supplemental Figure 10A).…”
Section: A Major Proportion Of the Cyp76c1-derived Linalool Oxides Issupporting
confidence: 61%
See 3 more Smart Citations
“…The linalool conjugates were exclusively detected as putative linalyl-hexose and linalyl-malonyl hexoses, as previously observed Yang et al, 2013). They accumulated at up to 5 times higher concentrations in the cyp76c1 lines, and their levels were significantly reduced in the complemented/35S:CYP76C1 line compared with the wild type ( Figure 6; Supplemental Figure 10A).…”
Section: A Major Proportion Of the Cyp76c1-derived Linalool Oxides Issupporting
confidence: 61%
“…Thus, it seems that the roles of linalool differ depending on the plant-insect interactions. Interestingly, Yang et al (2013) reported that thrips were first attracted by linalool emitted by engineered chrysanthemum expressing linalool/nerolidol synthase from strawberry (Fa-NES1) but were ultimately repelled by linalool conjugates. The role of linalool conjugates and linalool oxides in ecological interactions is still a matter of debate (Raguso and Pichersky, 1999).…”
Section: Cyp76c1 Influences the Interactions Of Flowers With Insectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of this gene in the plastids of chrysanthemum plants resulted in linalool emissions and accumulation of several forms of linalool glycosides. During the first 15 min, WFT significantly preferred these FaNES1 plants, but in the next 24 h gradually changed their preference to the wild type 52 . Recently, Shinoyama et al 53 developed genetically modified chrysanthemums by introducing a modified cry1Ab gene of Bacillus thuringiensis var.…”
Section: Chrysanthemum (Dendranthema Grandiflora)mentioning
confidence: 99%